2015
DOI: 10.1186/s12968-014-0095-8
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific association between distal aortic pulse wave velocity and peripheral arterial stenosis severity: a prospective cardiovascular magnetic resonance study

Abstract: BackgroundVascular disease expression in one location may not be representative for disease severity in other vascular territories, however, strong correlation between disease expression and severity within the same vascular segment may be expected. Therefore, we hypothesized that aortic stiffening is more strongly associated with disease expression in a vascular territory directly linked to that aortic segment rather than in a more remote segment. We prospectively compared the association between aortic wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Similarly another Rotterdam study showed a significant correlation between carotid plaque and aortic PWV which was lost after adjusting for cardiovascular risk factors [ 6 ]. Limitations of these latter studies is their correlation of one regional measure of arterial stiffness with plaque volume measured in a separate region, however atherosclerosis in one region poorly correlates with disease in other regions [ 8 , 26 ]. In addition these studies examined populations at high risk for or with known cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly another Rotterdam study showed a significant correlation between carotid plaque and aortic PWV which was lost after adjusting for cardiovascular risk factors [ 6 ]. Limitations of these latter studies is their correlation of one regional measure of arterial stiffness with plaque volume measured in a separate region, however atherosclerosis in one region poorly correlates with disease in other regions [ 8 , 26 ]. In addition these studies examined populations at high risk for or with known cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Bosch et al discovered that the mean MRA stenosis class (i.e., average stenosis severity visually scored over 27 standardized segments across the body) was a significant independent predictor for all-cause mortality [ 88 ]. They also found that MRA-derived PAD stenosis correlated well with distal aortic stiffness but to a lesser extent with proximal aorta stiffness [ 89 ]. Besides symptomatic PAD patients, MRI has also been used to examine peripheral arterial plaques in non-symptomatic subjects.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Expression of the disease in one location may not represent disease severity in other vascular territories although strong correlation between disease expression and severity within the same vascular segment may be expected. The authors prospectively compared the association between distal aortic stiffness measured by CMR pulse wave velocity (PWV) with the severity of peripheral arterial occlusive disease [135]. Atherosclerotic markers sampled in remote vascular territories such as PWV in the proximal aorta and left common carotid artery wall thickness was also compared.…”
Section: Vascular Diseasementioning
confidence: 99%